(untitled) (Research, Society and Development, 2023)
Objective: To investigate whether there is an association between the excessive use of smartphones and painful symptomatology in university students. Methods: It was a descriptive, transversal, observational field research, with an analytical quantitative and qualitative approach, carried out with 22 students dependent on the use of smartphones, from a private Higher Education Institution in the city of Santarém-Pará. A sociodemographic questionnaire, the Smartphone Dependency scale (EDS), the Corlett and Manenica Diagram and the manual evaluation of the tension points of the cervical muscles, shoulders and upper limbs were used. Results: In the sample, the female gender prevailed (86.36%; p = 0.0014) and the age group from 21 to 30 years (68.18%; p = 0.0024). The number of participants with tension points was expressive in musculature: trapezius upper fibers, wrist extensors and flexors. The most frequent pains were in the neck / cervical region and there was a significant association between smartphone dependence and pain in the cervical region (p = 0.0307). Conclusion: The most common painful symptomatology was in the neck / cervical region, with a significant association for smartphone dependence.